(untitled) (Journal of Contemporary Studies, 2021)
This study highlights the peril of Indian media’s insinuation of war with Pakistan in the aftermath of Uri incident of September 18, 2016. Uri was a violent expression of Kashmiri right of self-determination; but Indian media became a source of arousing anti-Pakistan hysteria for Indian public. The war frenzy created by the media, pressured Indian decision makers into making the claim of carrying out surgical strikes across the Line of Control (LoC). In this way, Indian media became a source of fomenting war between the two nuclear armed states. The study uses Indian sources to evidence the jingoistic frenzy of the Indian TV news channels. Importance of having responsible media in nuclear armed states has been underscored by Indian media’s dangerous handling of Uri crisis. This study raises awareness about the responsibility of media in sustaining peace between the nuclear rivals, particularly during crisis situations.